2006
DOI: 10.1007/s00712-005-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Welfare Effects of Cost Reductions in a Cournot Oligopoly

Abstract: cost reduction, oligopoly, technological spillover, welfare, D43, L13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our contribution extends the literature on the welfare impacts of cost asymmetries across firms (Lahiri and Ono, 1988;Zhao, 2001;Smythe and Zhao, 2006;Wang and Zhao, 2007). The existing contributions study the effects of a cost reduction in linear Cournot markets when firms have exogenous and asymmetric production costs.…”
Section: Related Literaturementioning
confidence: 81%
See 1 more Smart Citation
“…Our contribution extends the literature on the welfare impacts of cost asymmetries across firms (Lahiri and Ono, 1988;Zhao, 2001;Smythe and Zhao, 2006;Wang and Zhao, 2007). The existing contributions study the effects of a cost reduction in linear Cournot markets when firms have exogenous and asymmetric production costs.…”
Section: Related Literaturementioning
confidence: 81%
“…Lahiri and Ono (1988), Zhao (2001), Smythe and Zhao (2006) and Wang and Zhao (2007) also found that a technological improvement in an inefficient firm may reduce total surplus. Intuitively, the reason is that this improvement leads to a shift in production from a more efficient to an inefficient firm, with an increase in average production costs.…”
Section: Increases Total Surplus If Affecting Firm L If and Only If Tmentioning
confidence: 96%